1993
DOI: 10.1176/ajp.150.4.650
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of light therapy in seasonal affective disorder

Abstract: The authors report the frequency of side effects of light therapy in 105 patients with seasonal affective disorder treated with three intensities of light. Common symptoms to emerge during treatment were headache (19%), eyestrain (17%), and feeling "wired" (14%). There was no relationship between side effects and intensity of light used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(10 citation statements)
references
References 3 publications
3
7
0
Order By: Relevance
“…This discrepancy may be due to any of the three principal methodological differences from the aforementioned studies – a single exposure, comparison to a dim light control, and a sample of healthy young adults. However, the current results are highly consistent with the only other placebo-controlled study of adverse LT effects [41] in the extant literature. As in the present investigation, Volz and colleagues observed no significant differences in the side effects engendered by bright light versus dim red light.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This discrepancy may be due to any of the three principal methodological differences from the aforementioned studies – a single exposure, comparison to a dim light control, and a sample of healthy young adults. However, the current results are highly consistent with the only other placebo-controlled study of adverse LT effects [41] in the extant literature. As in the present investigation, Volz and colleagues observed no significant differences in the side effects engendered by bright light versus dim red light.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, this study observed no significant differences in side effects between the LT and placebo groups, although it is worth noting that the dosage of light was considerably lower than that most commonly prescribed in contemporary practice. One additional study [41] examined the side effects of a head-mounted visor that delivered white light at illuminance levels of 60 lux, 600 lux, or 3500 lux, respectively. We do not regard this as an adequate test of LT effects, however, in as much as it utilized a non-standard light delivery method (visor) with considerably less empirical support.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the possibility exist of hypomanic switch in patients with BD with possible symptoms such as tachypsychia, logorrhea, increased energy and activity, irritability or aggression [27,48]. The other rare side effects of light therapy are: headache, eye strain, nausea and agitation [38,49,50]. In addition, despite traditionnal precautions in BLT studies including what we planned for this LuBi study, there does not seem to be any retinal toxicity associated with light therapy [51].…”
Section: Discussionmentioning
confidence: 99%
“…Regularly reported side effects are mild visual complaints, nausea, dizziness and headaches, tired eyes, agitation, sleep disturbances, or, very rarely, (hypo) manic decompensation 23,101,102. (Relative) contraindications are preexisting retinal diseases, the use of photosensitizing drugs, and recent eye surgery 23.…”
Section: Light Treatmentmentioning
confidence: 99%